Bactericidal activity of fractionated granule contents from human polymorphonuclear leukocytes: antagonism of granule cationic proteins by lipopolysaccharide. - Modrzakowski, M C (1979)
Granule extracts from human polymorphonuclear leukocytes (PMN) were prepared with 0.2 M (pH 4.0) acetate. A fraction (valley AB) with distinctive bactericidal activity against cell wall mutants of Salmonella typhimurium LT-2 was obtained after fractionation of the granule extracts by Sephadex G-100 column chromatography. The smooth parent LT-2 strain was less sensitive to the bactericidal action. Susceptibility of the rough mutants to bactericidal action increased as sugar residues decreased in the lipopolysaccharide (LPS) (Re greater than Rd2 greater than Rd1 greater than Rc greater than Ra). Cationic protein(s) responsible for bactericidal activity could be selectively removed from the fraction by absorption with whole LT-2 cells or purified LPS. Loss of cationic protein species was confirmed by cationic polyacrylamide gel electrophoresis. Purified LPS from LT-2 or the deep rough mutant TA2168 inhibited the antimicrobial activity of the killing fraction in in vitro assays. A minor protein species (vAB1) from the valley AB fraction had an apparent molecular weight of 36,000 to 37,000 and represented a major bactericidal activity of the fraction. Small amounts of the isolated vAB1 protein were bactericidal for the smooth parent LT-2 strain.